2020
DOI: 10.1042/bsr20200218
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in ascending thoracic aortic aneurysms

Abstract: Thoracic Aortic Aneurysm (TAA) is characterized by the dilation of the aorta and is fatal if not diagnosed and treated appropriately. The underlying genetic mechanisms have not been completely delineated so better knowledge of the physiopathology of TAAs is needed to improve detection and therapy. MicroRNAs regulate gene expression post-transcriptionally and are known to be involved in cardiovascular diseases. The current study aimed to identify miRNAs that can be used as possible biomarkers for the early diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 77 publications
3
11
0
Order By: Relevance
“…CircRNAs can competitively bind to the miRNAs to alleviate the degeneration of the gene expression 21,22 . Differential expression of miRNAs has been previously reported in an aneurysmal sample and found to be associated with SMC apoptosis, inflammatory response, and ECM degradation in the aneurysm site 23–25 . In our study, we were able to confirm that circ_0008285 directly binds to miR‐150‐5p.…”
Section: Discussionsupporting
confidence: 78%
“…CircRNAs can competitively bind to the miRNAs to alleviate the degeneration of the gene expression 21,22 . Differential expression of miRNAs has been previously reported in an aneurysmal sample and found to be associated with SMC apoptosis, inflammatory response, and ECM degradation in the aneurysm site 23–25 . In our study, we were able to confirm that circ_0008285 directly binds to miR‐150‐5p.…”
Section: Discussionsupporting
confidence: 78%
“…17 Boon et al, 18 based on animal models, showed that miRNA 29 inhibition with an-timiR (anti-miRNA) 29 agents, led to decreased MMP 2 and 9 expression in the aorta, increased expression of collagen and elastin genes and limitation of aneurysm progression. These results were confirmed by the Maegdefessel et al study, 19 where antimiR29 agents in murine models increased collagen production, inducing a fibrotic response in the aortic wall and, hence, slowed down aneurysm evolution. 20 miRNA 195 is also involved in extracellular matrix regulation.…”
Section: Discussionsupporting
confidence: 59%
“…Meanwhile, elevated fibrillin-1 was proposed to be a possible biomarker for TAA due to its role as a scaffold protein for elastin in the aortic wall [ 23 ]. Several other potential biomarkers for TAA such as matrix metalloproteinases (MMPs) and miRNAs (hsa-miR-140-5p, hsa-miR-191-5p and hsa-miR-214-3p) have been reported [ 24 , 25 ]. Nonetheless, none of these proteins/molecules have been shown to have good diagnostic and/or predictive values for aortic aneurysms clinically in patients.…”
Section: Introductionmentioning
confidence: 99%